Prevalence and determinants of high-risk obstructive sleep apnea among hypertensive patients in referral hospitals of the Amhara Region, Northwest Ethiopia, 2022 - Kassaw, Meseret; Ayal, Bezawit Mulat; Chilot, Dagimawi; Abebaw, Kassa; Ashenef, Baye (Frontiers in Sleep, 2025)
BackgroundObstructive sleep apnea results from intermittent airway collapse during sleep. Despite its health risks, the prevalence and associated factors of OSA among hypertensive patients in Ethiopia remain unexplored.ObjectiveThis study assessed the prevalence and associated factors of high-risk OSA among hypertensive patients in referral hospitals within the Amhara Region, Northwest Ethiopia, in 2022.MethodsA cross-sectional study was conducted in selected referral hospitals from 21 April to 14 June 2022. A systematic random sampling technique was employed. Data were collected through structured, pretested, interviewer-administered questionnaires, file reviews, and physical examinations. Data were entered in Epi-Data 4.6 and analyzed using Stata 14. Logistic regression was performed, and variables with p < 0.05 were regarded as significantly associated with high-risk OSA.ResultsOf the 412 participants (97% response rate), the mean age was 58.95 ± 12.6 years, with 55.1% being female. The prevalence of high-risk OSA was determined to be 43.93% (95% CI: 39.2–48.8). Significant factors included age > 65 years (AOR = 8.00, 95% CI: 4.48–14.14), diabetes mellitus (AOR = 4.7, 95% CI: 2.48–8.94), male sex (AOR = 4.2, 95% CI: 2.38–7.45), and large neck circumference (AOR = 3.13, 95% CI: 1.27–7.74).ConclusionHigh-risk OSA is prevalent among hypertensive patients, particularly in older males and those with diabetes or a large neck circumference. Routine OSA screening should be integrated into hypertension care. Future studies should utilize gold-standard tools and explore cause-and-effect relationships.